2022
DOI: 10.3389/fnhum.2022.798883
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Brain-Computer Interface in Upper Limb Dysfunction After Stroke: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: ObjectiveThis study aimed to examine the effectiveness and safety of the Brain-computer interface (BCI) in treatment of upper limb dysfunction after stroke.MethodsEnglish and Chinese electronic databases were searched up to July 2021. Randomized controlled trials (RCTs) were eligible. The methodological quality was assessed using Cochrane’s risk-of-bias tool. Meta-analysis was performed using RevMan 5.4.ResultsA total of 488 patients from 16 RCTs were included. The results showed that (1) the meta-analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…An interesting result was that the control group showed a significant response in two of the four scales for the primary outcome (MAL-qualitative and quantitative and in the BBT), with the effect size for the experimental group being larger. Similar results were observed in a randomized clinical trial using BCI in combination with other therapies, where both groups showed functional improvement after the interventions (55). However, the functional gains obtained on standardized scales were greater in the experimental group, demonstrating the positive role of BCI in post-stroke rehabilitation.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…An interesting result was that the control group showed a significant response in two of the four scales for the primary outcome (MAL-qualitative and quantitative and in the BBT), with the effect size for the experimental group being larger. Similar results were observed in a randomized clinical trial using BCI in combination with other therapies, where both groups showed functional improvement after the interventions (55). However, the functional gains obtained on standardized scales were greater in the experimental group, demonstrating the positive role of BCI in post-stroke rehabilitation.…”
Section: Discussionsupporting
confidence: 83%
“…Brain-computer interface is a promising strategy for treating and recovering functions, specifically UL motor skills ( 55 ). A meta-analytic study with 235 subjects suggested that BCI may be an effective intervention for post-stroke UL motor rehabilitation ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These terms include “signal possessing” or “signal analysis” [ 6 , 7 , 19 , 52 ]. Medical-associated words such as “stroke” and “rehabilitation” were seen to remain in use [ 64 , 71 , 76 , 78 , 85 ]; this is reflected in the shift of focus from understanding how the brain functions after a stroke to more practical applications identifying functional brain pathways using“motor imagery” [ 7 , 36 , 70 , 79 , 89 ] and its practical application with “upper limb” [ 84 , 85 ], or “upper extremity” [ 86 ] and “lower limb” [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…EEG has also been used to detect mental commands for the operation of wheelchairs after spinal cord injury or neuromuscular disease and has extensively been used in stroke rehabilitation and external device control [35,43]. EEG systems in stroke victims have been efective in returning upper body control after rehabilitation [76,[83][84][85][86].…”
Section: Marketing and Advertisingmentioning
confidence: 99%